Love and revolution (about "La hija de Marx", by Clara Obligado, and "El viajero del siglo", by Andrés Neuman) - Drucaroff, Elsa (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
The article does a comparative analysis of two very contemporary Argentine novels: La hija de Marx, by Clara Obligado, and El viajero del siglo, by Andrés Neuman, both written by two Argentine writers who had to make their homes in Spain. Both books are sui generis historical novels and examples of the «holey realism», a representative esthetics of the current Argentine narrative. Both novels implicate the social and political change and the experimentation on gender relationships and pleasure of the bodies. Both novels accept a reading related with the concept of the Symbolic Order of the Mother.
Keywords: Argentine novel; Clara Obligado; Andrés Neuman; historical novel; holey realism; gender; erotism